2017
DOI: 10.1016/j.addbeh.2017.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Problematic internet users' skin conductance and anxiety increase after exposure to the internet

Abstract: These results suggest that, following termination of an internet session, withdrawal-like effects are seen, both psychologically and physiologically.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
24
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 34 publications
1
24
2
1
Order By: Relevance
“…[1][2][3][4][5][6] There is a consensus that problematic internet use (PIU) is characterized by overuse of the internet with associated impairment(s) across various domains of functioning. [1-4, 7, 8] Some have gone further, suggesting that PIU is a behavioral version of a substance-use disorder, [9][10][11] while others have suggested that it is either an impulse-control disorder, [3,12,13] or a subtype of obsessivecompulsive disorder, [14,15] although empirical evidence for these designations is lacking. [8,10,[16][17][18][19][20] Regardless of whether PIU truly constitutes a form of addiction, there is a need to obtain a more complete empirical understanding of the contexts in which it arises in childhood and adolescence, as well as its unique contributions to socio-emotional and behavioral functioning.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6] There is a consensus that problematic internet use (PIU) is characterized by overuse of the internet with associated impairment(s) across various domains of functioning. [1-4, 7, 8] Some have gone further, suggesting that PIU is a behavioral version of a substance-use disorder, [9][10][11] while others have suggested that it is either an impulse-control disorder, [3,12,13] or a subtype of obsessivecompulsive disorder, [14,15] although empirical evidence for these designations is lacking. [8,10,[16][17][18][19][20] Regardless of whether PIU truly constitutes a form of addiction, there is a need to obtain a more complete empirical understanding of the contexts in which it arises in childhood and adolescence, as well as its unique contributions to socio-emotional and behavioral functioning.…”
Section: Introductionmentioning
confidence: 99%
“…reported PIU was available for children of all ages in the sample(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21), self-reported questionnaires were only administered to children ages 7 and up. Fourth, the HBN sample is largely composed of individuals affected by one or more mental health or learning disorders, inherently increasing thelikelihood of problematic behaviors among participants.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6] There is a consensus that problematic internet use (PIU) is characterized by overuse of the internet with associated impairment(s) across various domains of functioning. [1][2][3][4]7,8 Some have gone further, suggesting that PIU is a behavioral version of a substance-use disorder, [9][10][11] while others have suggested that it is either an impulse-control disorder, 3,12,13 or a subtype of obsessive-compulsive disorder, 14,15 although empirical evidence for these designations is lacking. 8,10,[16][17][18][19][20] Regardless of whether PIU truly constitutes a form of addiction, there is a need to obtain a more complete empirical understanding of the contexts in which it arises in childhood and adolescence, as well as its unique contributions to socio-emotional and behavioral functioning.…”
Section: Introductionmentioning
confidence: 99%
“…not certified by peer review) (which was The copyright holder for this preprint this version posted October 8, 2019. . https://doi.org/10.1101/19005967 doi: medRxiv preprint all ages in the sample(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21), self-reported questionnaires were only administered to childrenages 7 and up. Fourth, the HBN sample is largely composed of individuals affected by one or more mental health or learning disorders, inherently increasing the likelihood of problematic behaviors among participants.…”
mentioning
confidence: 99%
“…In future work, the acquisition of activity-specific measures would be helpful in discerning differences in patterns of association between mental health disorders and specific forms of internet addiction (e.g., videogaming, pornography, gambling). Third, while parent-reported PIU was available for children of all ages in the sample(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21), self-reported questionnaires were only administered to children ages 7 and up. Fourth, the HBN sample is largely composed of individuals affected by one or more mental health or learning disorders, inherently increasing the likelihood of problematic behaviors among participants.…”
mentioning
confidence: 99%